2000
DOI: 10.1046/j.1523-1755.2000.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

cAMP stimulates the in vitro proliferation of renal cyst epithelial cells by activating the extracellular signal-regulated kinase pathway

Abstract: : We conclude that cAMP agonists stimulate the proliferation of ADPKD but not HKC epithelial cells through PKA activation of the ERK pathway at a locus distal to receptor tyrosine kinase. We suggest that the adenylyl cyclase signaling pathway may have a unique role in determining the rate of cyst enlargement in ADPKD through its actions to stimulate cellular proliferation and transepithelial solute and fluid secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
259
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(289 citation statements)
references
References 36 publications
24
259
2
2
Order By: Relevance
“…Also, the intracellular cAMP level has been reported to be increased in various models of PKD (20). Although cAMP inhibits the Raf-1/ERK pathway in normal epithelial cells, Yamaguchi et al (21,22) found that cAMP and adenylyl cyclase agonists stimulated the proliferation of cyst epithelial cells that were cultured from kidneys of patients with ADPKD by activating ERK via B-Raf. Furthermore, Chatterjee et al (23) reported that a glycosphingolipid lactosylceramide is upregulated in proximal tubular cells from human PKD kidneys and may stimulate cell proliferation via ERK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the intracellular cAMP level has been reported to be increased in various models of PKD (20). Although cAMP inhibits the Raf-1/ERK pathway in normal epithelial cells, Yamaguchi et al (21,22) found that cAMP and adenylyl cyclase agonists stimulated the proliferation of cyst epithelial cells that were cultured from kidneys of patients with ADPKD by activating ERK via B-Raf. Furthermore, Chatterjee et al (23) reported that a glycosphingolipid lactosylceramide is upregulated in proximal tubular cells from human PKD kidneys and may stimulate cell proliferation via ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action is thought to be blockade of cAMP. ERK is the downstream target of cAMP in the cyst epithelium in PKD (20,21). Because targeting a downstream step generally is more efficient and more specific, inhibition of the ERK pathway may provide a promising approach to the treatment of PKD.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications of the ERK pathway are different from observations in cultured renal cells. Yamaguchi et al (44) showed that the cAMP-dependent proliferation of cultured human ADPKD cyst-lining cells is mediated through phosphorylation/activation of ERK. By contrast, cAMP inhibits ERK activity and slows proliferation in normal epithelial cells from human kidney cortex.…”
Section: Discussionmentioning
confidence: 99%
“…However, if we assume that the primary defect in type 2 ADPKD is PKD2-mediated Ca 2+ influx (and not Na + or K + which also pass through PKD2), it is possible that a connection between a Ca 2+ channel and cAMP can be made. It has been reported that cystic cells have abnormally high levels of cAMP [79][80][81][82] and the administration of a vasopressin V2 receptor antagonist, which reduced cAMP, suppressed the cystic phenotype in PKD2 knock out mice [83] and other animal models [84,85]. It is also known that store-operated Ca 2+ channels are directly coupled to specific isoforms of adenylyl cyclases [86][87][88].…”
Section: Pkd2-mediated Signal Transductionmentioning
confidence: 99%